Optimizing airway management and anesthetic techniques in maxillofacial procedures - Alam, Mohammed Badrul; Sultana, Shamim Ara; Alam, M. Hassanul; Tasnim, Rahnuma; Ahmed, M. Shakil; Chowdhury, Mohammad Rashal; Arzoo, Shabera; Bhowmick, Dilip Kumar; Kamal, Mustafa (International Surgery Journal, 2025)
Background: Airway management of maxillofacial trauma, such as road accidents, falls and violence, is challenging, especially when facial fractures or soft tissue injuries prevent conventional intubation. Preventions such as nasal and fibreoptic-guided intubation prevent complications to avoid tracheostomy. This study aimed to evaluate the efficacy of various airway management methods for improving patient outcomes after maxillofacial trauma. Methods: This retrospective observational study was conducted at Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2017 to December 2019. A total of 150 patients who underwent maxillofacial surgery were included in this study. The etiology and types of trauma, airway management approaches (nasal intubation, oral intubation, fiberoptic guided intubation and tracheostomy) and anesthesia outcomes were identified. Descriptive statistics, t-tests and chi-square tests were performed for the statistical analysis. Results: Of the 150 patients, 56% underwent nasal intubation, 19.3% underwent oral intubation and 24.7% underwent fiberoptic-guided intubation. Oral access was limited; however, nasal intubation was predominant and provided stable airway management. In 17.3% of the cases, fiberoptic-guided intubation with sedation provided a minimally invasive option with improved visualization. Importantly, none of the patients were tracheostomized, confirming the efficacy of nonsurgical techniques. Conclusions: Safe and effective airway management techniques utilized in nasal and fiberoptic-guided intubation for maxillofacial trauma patients were shown to reduce the need for invasive procedures, such as tracheostomy. The use of these minimally invasive methods improves patient outcomes by improving airway control and decreasing complications in cases of complex trauma.